Ventricular cerebrospinal fluid melatonin concentrations investigated with an endoscopic technique - Longatti, Pierluigi; Perin, Alessandro; Rizzo, Vittoria; Comai, Stefano; Giusti, Pietro; Costa, Carlo Virgilio Luigi (Journal of pineal research, 2007)
:  The role of melatonin in humans still remains unclear. Uncertainties persist about its effects on neurophysiology regarding its levels in human cerebrospinal fluid (CSF), as the bulk of knowledge on this subject mainly derives from studies conducted on animals. In this study, CSF was micro‐sampled with a simple, new method from each cerebral ventricle of patients undergoing neuroendoscopy for hydrocephalus. Our purpose was to measure CSF melatonin levels and determine possible differences in its concentration among various significant areas in the cerebral ventricles (e.g. pineal recess, pituitary recess, lateral ventricle, fourth ventricle) and lumbar cistern. From 2002 to 2004, 10 hydrocephalic patients were operated on using a neuroendoscopic technique. The CSF specimens were investigated for melatonin concentrations (free plus protein‐bound) after deproteinization; the measurement technique was high‐performance liquid chromatography. The preliminary data obtained with this endoscopic micro‐sampling technique (applied to humans for the first time) suggest that melatonin is more concentrated within the ventricles and its highest concentration is found in the third ventricle (IIIv), although the difference detected between the CSF of the IIIv and that of the pineal recess was not significant.